Estimating the effect of aqueous cationic latex from the class of thermal elastic plastics on the properties of bitumen emulsions - Zhdaniuk, Valeriy; Novakovska, Victoria (Eastern-European Journal of Enterprise Technologies, 2021)
To produce cationic bitumen emulsions, bitumen is used, whose penetration is not lower than 90 mm-1. Such bitumen has a small plasticity interval, which leads to a deterioration in its heat resistance at elevated temperatures and narrows the scope of application of emulsions based on it. Based on the review of emulsion modification methods, the modification has been proposed that involves mixing the finished bitumen emulsions with aqueous cationic latex. The process of interaction between a bituminous emulsion and an aqueous cationic latex has been considered. A mechanism for the disintegration of the modified bitumen emulsion on the surface of mineral materials was proposed. The emulsifiers have been selected and the composition of the aqueous phase has been chosen based on the analysis of surface tension isotherms. The influence of the modification on the properties of bitumen emulsions was investigated. It was established that the main physicochemical characteristics of the interphase surface accept similar values for the aqueous phase and emulsions based on it. It has been proven that the introduction of aqueous cationic latex quite moderately affects the basic physical-mechanical properties of emulsions, which makes it possible not to change the main technological parameters when using them. It was established that increasing the concentration of the polymer in the emulsion has a positive effect on the physical-mechanical properties of the binder. With an increase in the concentration of the polymer to 6 % the softening temperature increases by 16 °C, elasticity is 74 %, and the holding capacity at minus 25 °C is approaching 100 %. Improving the physical-mechanical properties of residual binder as a result of emulsion modification could increase the durability of layers in a roadbed based on bitumen emulsions and expand the scope of their application in the construction and repair of motorways